2020
DOI: 10.3390/ijms21218039
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Small Noncoding RNA in DNA Double-Strand Break Repair

Abstract: DNA damage is a common phenomenon promoted through a variety of exogenous and endogenous factors. The DNA damage response (DDR) pathway involves a wide range of proteins, and as was indicated, small noncoding RNAs (sncRNAs). These are double-strand break-induced RNAs (diRNAs) and DNA damage response small RNA (DDRNA). Moreover, RNA binding proteins (RBPs) and RNA modifications have also been identified to modulate diRNA and DDRNA function in the DDR process. Several theories have been formulated regarding the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 91 publications
(173 reference statements)
0
19
0
Order By: Relevance
“…DilncRNAs are transcribed from and toward DNA ends whenever RNAP II binds to break-associated MRN (Figure 3B) (Michelini et al, 2017;Sharma et al, 2021). They have important roles in the recruitment of DSB signaling factors and also serve as precursors for the Drosha and Dicer-dependent generation of DNA damage response small RNAs (DDRNAs) (Francia et al, 2012;Michelini et al, 2017;Rossiello et al, 2017;Gioia et al, 2019;Rzeszutek and Betlej, 2020).…”
Section: Rna-binding Protein-rna Interactions Are Central To Double-strand Break Signaling and Repairmentioning
confidence: 99%
See 1 more Smart Citation
“…DilncRNAs are transcribed from and toward DNA ends whenever RNAP II binds to break-associated MRN (Figure 3B) (Michelini et al, 2017;Sharma et al, 2021). They have important roles in the recruitment of DSB signaling factors and also serve as precursors for the Drosha and Dicer-dependent generation of DNA damage response small RNAs (DDRNAs) (Francia et al, 2012;Michelini et al, 2017;Rossiello et al, 2017;Gioia et al, 2019;Rzeszutek and Betlej, 2020).…”
Section: Rna-binding Protein-rna Interactions Are Central To Double-strand Break Signaling and Repairmentioning
confidence: 99%
“…At DSBs, RNAP II also promotes the generation of DSBinduced RNAs (diRNAs), which are produced when local RNA transcripts become double-stranded and are then processed by Dicer into double-stranded small RNAs (Wei et al, 2012;Yang and Qi, 2015;Rzeszutek and Betlej, 2020). In Arabidopsis thaliana, the generation of double-stranded RNAs depends on RNA-dependent RNA polymerases that use RNA transcripts as templates (Wei et al, 2012;Miki et al, 2017;Rzeszutek and Betlej, 2020). However, how single-stranded RNA transcripts become double-stranded RNAs in human cells remains unclear.…”
Section: Rna-binding Protein-rna Interactions Are Central To Double-strand Break Signaling and Repairmentioning
confidence: 99%
“…RNA transcripts and DDR proteins are known to interact functionally (40). Many recent studies have reported the pivotal role of ncRNAs in DNA repair and genomic rearrangements in different research models (41)(42)(43)(44). There is growing evidence that ncRNAs regulate the DDR, especially small microRNAs (miRNAs), which are induced at DNA-DSBs, thus mediating repair (23,41,45).…”
Section: The Underestimated Role Of Small Ncrnas In Dna Damage Response and Repairmentioning
confidence: 99%
“…Many recent studies have reported the pivotal role of ncRNAs in DNA repair and genomic rearrangements in different research models (41)(42)(43)(44). There is growing evidence that ncRNAs regulate the DDR, especially small microRNAs (miRNAs), which are induced at DNA-DSBs, thus mediating repair (23,41,45). Regulatory short miRNAs are ncRNAs encoded in intronic regions of proteincoding genes or in the intergenic regions of the genome (23,42).…”
Section: The Underestimated Role Of Small Ncrnas In Dna Damage Response and Repairmentioning
confidence: 99%
See 1 more Smart Citation